PENERAPAN MODEL COOPERATIVE LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERMAIN SEPAKBOLA DAN KERJASAMA SISWA DI SMPN 2 LEMBANG - Luvian, Lulu; Juliantine, Tite (Jurnal Olahraga, 2017)
The purpose of this research is to find out how the influence of the implementation of cooperative learning models to improve football playing skills and student cooperation at SMPN 2 Lembang. This study uses a classroom action research (CAR) method and uses a classroom action research design (CAR). The sample used in this study was 10% of the population representing 36 students. In the initial test of playing skills and cooperation, students get an average score of 24% for playing skills and 22% for collaboration. In cycle I, action I increased to 30% for play skills and 32% for cooperation, in cycle I, action II increased to 50% for play skills and 50% for cooperation, in cycle II, action I increased scores to 65% skills play and 66% for cooperation, in the second cycle of action II there was an increase of 82% for playing skills and 82% for cooperation so that it was seen an increase in each cycle in this study. Then it can be concluded that there is significant progress in the application of cooperative learning models to improve soccer playing skills and student cooperation at SMPN 2 Lembang.